Population genetics of the frog-killing fungus Batrachochytrium dendrobatidis - Morgan, Jess A. T. (National Academy of Sciences, 2007)
Global amphibian decline by chytridiomycosis is a major environmental disaster that has been attributed to either recent fungal spread or environmental change that promotes disease. Here, we present a population genetic comparison of Batrachochytrium dendrobatidis isolates from an intensively studied region of frog decline, the Sierra Nevada of California. In support of a novel pathogen, we find low diversity, no amphibian-host specificity, little correlation between fungal genotype and geography, local frog extirpation by a single fungal genotype, and evidence of human-assisted fungus migration. In support of endemism, at a local scale, we find some diverse, recombining populations. Therefore neither epidemic spread nor endemism alone explains this particular amphibian decline. Recombination raises the possibility of resistant sporangia and a mechanism for rapid spread as well as persistence that could greatly complicate global control of the pathogen.